STUDI KERAPATAN PHYLUM ECHINODERMATA PADA ZONA INTERTIDAL PANTAI INDAH KELURAHAN TANJUNG KRAMAT KOTA GORONTALO. - Latjompoh, Masra (Sainstek, 2009)
This research purposed to know how the density of phylum echinodermata in intertidal zona pantai indah Tanjung Kramat. Gorontalo city. This research is descriptive kuantitative, research with survey methode do observe the data directly. Time of research in two days in night time, taking sample of objects doing in all of points of samples using kuadran size 20x20 meter. Each of classes spesies of objects in kuadran, counted and noted then entried in the place. Identification doing in the lab. The result of the research shown that phylum echinodermata with the highest density index is ophiuroidea, with density indeks 0,375indv/m2 and the lowst is population of holoturoidea with density indeks 0,007 indv/m2.